Split cornea transplantation in anterior lamellar keratoplasty for limbal dermoid surgery: a case report (Medical Journal of Indonesia, 2023)
Limbal dermoid is a rare congenital lesion that can impair vision and raise aesthetic concerns. Surgery is frequently required to reduce discomfort and enhance visual outcomes. A 20-year-old woman presented with a limbal dermoid measuring 4.5 mm in diameter and half the depth of the stroma. Excision was performed with anterior lamellar keratoplasty (ALK) using a post-Descemet's membrane endothelial keratoplasty graft, which resulted in signs of graft failure. Re-surgery was then performed with post-Descemet's stripping endothelial keratoplasty graft. It yielded a clear graft with good visual acuity. The first corneal graft utilized 95% of the graft thickness to cover 55% of the defect, leading to poor host-donor apposition. The second graft employed 55–65% to cover the same portion of the defect. The proportional thickness of the graft is crucial for a successful ALK. Split cornea transplantation produces respectable results; however, the corneal thickness must be carefully considered.